Discrepancy theory - Bilyk, Dmitriy; Dick, Josef; Pillichshammer, Friedrich (Radon series on computational and applied mathematics ;, 2020)
The contributions in this book focus on a variety of topics related to discrepancy theory, comprising Fourier techniques to analyze discrepancy, low discrepancy point sets for quasi-Monte Carlo integration, probabilistic discrepancy bounds, dispersion of point sets, pair correlation of sequences, integer points in convex bodies, discrepancy with respect to geometric shapes other than rectangular boxes, and also open problems in discrepany theory